A device for making tablets from herbal powders and method thereof. - Yusof, Yus Aniza; Chin , Nyuk Ling; Ahmad, Sobah; Abdullah, Rohaiza; Md Nor, Che Rodiziah (2009)

(untitled)
A device for making tablets according to any of the preceding claims characterized in that wherein a cylindrical stainless steel die is used and wherein the cylindrical stainless steel die is designed with a diameter of 13 to 20 mm and wherein the internal roughness of the die is designed to be approximately 0.3 centre average and at the interior surface of the cylindrical stainless steel die is designed to be shiny with mirror finished and wherein the main embodiment is the tabletting of selected herbs powders.